The Black studies reader - Bobo, Jacqueline; Hudley, Cynthia; Michel, Claudine (Routledge, 2004)
Black studies emerged from the tumultuous social and civil rights movements of the 1960s and empowered African Americans to look at themselves in new ways and pass on a dignified version of Black history. However, it also enriched traditional disciplines in profound and significant ways. Proponents of Black and ethnic studies confronted the false notion that scholarly investigations were objective and unbiased explorations of the range of human knowledge, history, creativity, artistry, and scientific discovery. As they protested against hegemonic notions like universal psychology and re-evaluated canonical texts in literature, a new model of academic inquiry evolved: one committed to serving a range of populations, that critiqued traditional politics, culture, and social affairs, and worked with activist energy for the transformation of the existing social order. With an all-star cast of contributors, The Black Studies Reader takes on the history and future of this multi-faceted academic field. Topics include Black feminism, cultural politics, Black activism, lesbian and gay issues, African American literature and film, education, and religion. This authoritative collection takes a critical look at the current state of Black studies and speculates on where it may go from here.
Keywords: LGBTQIA2+; afro-féminisme; amériques; approches et analyses; féminisme islamique; histoire et politique; identités LGBTQIA2+; militance; outils; ouvrages de références; racisme; ressource en ligne; régions géographiques; sexualité; système colonial; systèmes d'oppressions; thématiques; états-unis

Évaluation de l'implantation d'un projet d'éducation à la sexualité en regard des rôles et stéréotypes sexuels dans deux écoles primaires situées en Montérégie - Caron, Françoise; Moore, Danièle (Agence de développement de réseaux locaux de services de santé et de services sociaux de la Montérégie (Québec), 2004)
L'implantation du nouveau programme de formation de l'école québecoise et la redéfinition de l'entente de collaboration entre le ministère de l'Éducation du Québec et le ministère de la Santé et des Services sociaux sont la toile de fond de ce projet. En effet, dans le cadre de ce projet d'éducation à la sexualité, les élèves sont amenés à developper différentes compétences disciplinaires et transversales tout en abordant des ntions reliées aux rôles et stéréotypes sexuels. De plus, la réalisation des activités pédagogiques auprès des enfants repose sur la participation des enseignants et des enseignantes et implique la collaboration let le soutien des infirmières scolaires. Les processus d'adoption et de mise en oeuvre du projet ont été évalués pour connaître les conditions réussite de l'implantation dans deux écoles pilotes de la Montérégie. Le présent rapport rend compte des résultats de cette évaluation. Ceux-ci serviront à améliorer le guide pédagogique et à favoriser l'implantation des activités dans d'autres milieux. De plus, les résultats et les recommandations présentés dans ce rapport sont importants, non seulement pour la mise en oeuvre de ce type d'intervention reliée à l'éducation à la sexualité, mais aussi pour d'autres projets de prévention et de promotion de la santé qui pourraient s'inscrire dans le contexte d'une approche d'École en santé.
Keywords: 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; canada; discipline; montérégie; périodes historiques; québec; ressource en ligne; régions géographiques; science de l'éducation; sexisme; sexualité; stéréotypes de genre; systèmes d'oppressions; thématiques; éducation sexuelle

Stolen From Our Bodies: First Nations Two-Spirits/Queers and the Journey to a Sovereign Erotic - Driskill, Qwo-Li (Studies in American Indian Literatures, 2004)
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; autothéorie; cherokee; cours; discipline; féminisme autochtone; militance; premier cycle; premières nations; périodes historiques; queer; régions géographiques; sexualité; soc2014; système colonial; systèmes d'oppressions; thématiques; états-unis

Aberrations in Black: Toward a queer of color critique - Ferguson, Roderick A. (Critical American studies series, 2004)
A hard-hitting look at the regulation of sexual difference and its role in circumscribing African American culture. The sociology of race relations in America typically describes an intersection of poverty, race, and economic discrimination. But what is missing from the picture—sexual difference—can be as instructive as what is present. In this ambitious work, Roderick A. Ferguson reveals how the discourses of sexuality are used to articulate theories of racial difference in the field of sociology.
Keywords: amériques; approches et analyses; cours; discipline; discours dominant; fem1000; fem3300; histoire et politique; hétérosexisme; identités LGBTQIA2+; premier cycle; queer; queer of color; racisme; ressource en ligne; régions géographiques; sciences humaines; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; violences; états-unis

Gender, discourse, and desire in twentieth-century Brazilian women's literature - Pinto, Cristina Ferreira (Purdue studies in Romance literatures, 2004)
This study by Cristina Ferreira-Pinto explores the poetic and narrative strategies twentieth-century Brazilian women writers use to achieve new forms of representation of the female body, sexuality, and desire. Female writers discussed include: Gilka Machado, Lygia Fagundes Telles, Marcia Denser, and Marina Colasanti. While creating new forms, these writers are also deconstructing cultural myths of femininity and female behavior. In order to understand these myths, the book also presents new readings of some male-authored canonical novels by Jose de Alencar, Machado de Assis, Manuel Antonio de Almeida, and Aluisio Azevedo. The specific focus on female sexuality and desire acknowledges the intrinsic link between sexuality and an individual's sense of identity, and its importance for female identity, given the historical repression of women's bodies and the double standard of morality still pervasive in many Western cultures. In the discussion of the strategies Brazilian female poets and fiction writers employ, Ferreira-Pinto addresses some social and cultural issues that relate to a woman's sense of her own body and sexuality: the characterization of women based on racial features and class hierarchy; marriage; motherhood; the silencing of the lesbian subject; and aging. Ferreira-Pinto's analysis is informed by the works of various and diverse critics and theoreticians, among them Helene Cixous, Teresa De Lauretis, Adrienne Rich, Gloria Anzaldua, Georges Bataille, and Wilhelm Reich.
Keywords: amériques; arts; brésil; corps; discipline; histoire et politique; littérature; maternité; ressource en ligne; régions géographiques; sexualité; thématiques; violences; écriture des femmes*; études littéraires